Bagaimana Media Sosial Membentuk Minat Kunjungan Wisatawan: Peran Mediasi Persepsi Kognitif Dan Keterikatan Emosional Dalam Pariwisata Digital The Lodge Maribaya - Radians Krisna Febriandy; Tiara Maulinda Habibah; Asep Gumilar Hidayat; Kresno Yulianto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In the era of digital tourism, a lack of in-depth understanding of the psychological mechanisms of how social media shapes tourist interest poses a strategic challenge for tourism destination development. Most previous studies have been descriptive in nature without testing the causal relationships and mediating mechanisms underlying the tourist decision-making process. The phenomenon of “Instagramable destinations” has transformed the tourism marketing paradigm, but theoretical understanding of the cognitive and affective pathways linking social media exposure with behavioral intention remains limited. This study aims to analyze the influence of social media on tourist visitation interest through the mediation of cognitive perception and emotional attachment to the destination The Lodge Maribaya, Lembang. Specifically, specific, this study tests the dual-process mechanism in the context of digital tourism. The study employs a quantitative approach with an explanatory research design. Data were collected from 100 active social media users who had been exposed to content related to The Lodge Maribaya using purposive sampling with criteria of being aged 17–45 years. The research instrument consists of a Likert scale questionnaire with 28 items adapted from the current theoretical framework. Data analysis was conducted using Structural Equation Modeling (SEM) with SPSS 28.0 and AMOS 27.0 to test validity, reliability, and mediation analysis. The results of the analysis indicate that social media exposure significantly influences cognitive perception (β = 0.678; p < 0.001) and emotional attachment (β = 0.591; p < 0.001). Both variables also positively influence tourist visit interest, with an R² contribution of 0.684. Mediation analysis revealed that cognitive perception and emotional attachment partially mediate the effect of social media exposure on visit interest, confirming the dual-process theory in digital tourism.